Economical smart composting machine to manage food waste, alleviate environmental degradation and combat climate change on Penang Hill - Che Zalina Zulkifli (Tanjong Malim, 2019)
Economical smart composting machine to manage food waste, alleviate environmental degradation and combat climate change on Penang Hill by Che Zalina Zulkifli